Health Talk - The Star, (2008)
MALAYSIAN Healthy Aging Society is conducting a talk for members on Preventing Strokes at Dewan Putra 1, 9th Floor Grand Seasons Avenue (UPM Lecture Halls) Jalan Pahang KL on May 10 at 10.30am. The talk will be followed by a general meeting and refreshments. For details, call 03-2095 5600